2005
DOI: 10.1111/j.1365-3040.2005.01408.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of red, far‐red and blue light in maintaining growth in latitudinal populations of Norway spruce (Picea abies)

Abstract: Seedlings of trees with a free growth pattern cease growth when night-lengths become shorter than a critical value, and this critical night-length (CNL) decreases with increasing latitude of origin. In northern populations, the light quality also appears to play an important role and a clinal variation in requirement for far-red (FR) light has been documented. In this study we dissected the light quality requirements for maintaining growth in different latitudinal populations of Norway spruce ( Picea abies (L.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
82
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(94 citation statements)
references
References 27 publications
9
82
3
Order By: Relevance
“…In our study, a 1:1 mixture of BFr and RFr promoted significant stem elongation compared with plants under either FL or BR, but lateral branching and leaf unfolding were inhibited in all species (data not shown). Enhanced elongation mediated by far-red rather than red light has been reported in Norway spruce (Picea abies) (Molmann et al, 2006), as well as in Pelargonium 'Penny Irene ~ (Appelgren, 1991 Betula pendula, with this effect being significantly greater under continuous R+Fr radiation. However, we observed inhibited stem elongation with the BR treatment.…”
Section: Resultsmentioning
confidence: 94%
“…In our study, a 1:1 mixture of BFr and RFr promoted significant stem elongation compared with plants under either FL or BR, but lateral branching and leaf unfolding were inhibited in all species (data not shown). Enhanced elongation mediated by far-red rather than red light has been reported in Norway spruce (Picea abies) (Molmann et al, 2006), as well as in Pelargonium 'Penny Irene ~ (Appelgren, 1991 Betula pendula, with this effect being significantly greater under continuous R+Fr radiation. However, we observed inhibited stem elongation with the BR treatment.…”
Section: Resultsmentioning
confidence: 94%
“…Recent phylogenetic analyses demonstrate that plant phytochromes were acquired in the last common ancestor of Archaeplastida and that the canonical plant phytochromes originated in an ancestor of streptophytes (Duanmu et al, 2014;Li et al, 2015). Although R/FR photoreversible responses and the distribution of phytochrome genes have been reported in several angiosperms (Mancinelli, 1994), gymnosperms (Alosi and Neale, 1992;Christensen et al, 2002;Mølmann et al, 2006), ferns (Haupt, 1985;Tsuboi et al, 2012), bryophytes (Hartmann and Jenkins, 1984), and charophytes (Weisenseel and Ruppert, 1977;Sokol and Stross, 1992), little is known about the molecular mechanisms of phytochrome signaling apart from those of Arabidopsis. In this study, we found that phytochrome signaling in a liverwort is mediated by a single PIF transcription factor.…”
Section: Discussionmentioning
confidence: 99%
“…At the molecular level of signalling photoperiod input is via the phytochrome system (Olsen and Junttila 2002;Mølmann et al 2006;Taulavuori et al 2009). It then feeds into the CO/FT regulatory module (CO = CONSTANS, FT = FLOWERING LOCUS T, a floral integrator gene).…”
Section: And Responses Of Membranes Including Thylakoids Of Chloroplamentioning
confidence: 99%